2020
DOI: 10.3390/ma13020390
|View full text |Cite
|
Sign up to set email alerts
|

Under-Drilling versus Hybrid Osseodensification Technique: Differences in Implant Primary Stability and Bone Density of the Implant Bed Walls

Abstract: The goal of this study was to evaluate the effects of two implant bed preparation techniques on the implant primary stability (IPS) and the bone density of the implant site. We completed 40 implant bed osteotomies in pig ribs using two techniques: osseodensification (OD) plus under-drilling (UD) with universal osseodensification drills (Test A), and under-drilling alone with drills of the same implant system (Test B). Implants with a 4.1 mm diameter and 10 mm length were inserted, and the IPS was evaluated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 49 publications
2
17
0
6
Order By: Relevance
“…However, our results for the group for which the bed was prepared using a universal system for osteotomy (group G4) in low-density bone (block 1) showed values much lower than those shown for groups G2 and G3 (127.2% higher on average), where undersized instruments from the same manufacturer for the implant were used. These results corroborate the findings recently published by Delgado-Ruiz and collaborators [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, our results for the group for which the bed was prepared using a universal system for osteotomy (group G4) in low-density bone (block 1) showed values much lower than those shown for groups G2 and G3 (127.2% higher on average), where undersized instruments from the same manufacturer for the implant were used. These results corroborate the findings recently published by Delgado-Ruiz and collaborators [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, the authors did not compare their drill design with other drill designs. Furthermore, Antonelli et al [ 21 ] and Delgado-Ruiz et al [ 25 ], showed in experimental models in pig ribs that the counterclockwise drilling technique increased the bone density of the implant bed walls and that bone density was higher at the apical region (evaluated with µCT). Their results are in agreement with the results of the present work in regard to the apical area; however, no evidence of bone condensation was observed with any of the drills and rotation direction used in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of primary stability when using OD was observed in previous studies 14,18,23,32,35−38 , regardless of the implant's design or the implant surface 17,19,39 . Nevertheless, previous studies demonstrated that the densi cation of the bone interface does not guarantee adequate primary stability ex-vivo 15 and in vivo 40 because of high interfacial stresses that caused fractures and triggered a prolonged period of bone resorption. However, it was the rst time that such small implantimplant bed discrepancy was evaluated, and no brous tissue formation was identi ed at the boneimplant interface.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the concept of osseodensi cation (OD) was introduced aiming to improve the primary stability of implants placed in low-density bone sites 14 . OD is a surgical instrumentation technique where the bone is compacted into open marrow spaces during drilling, increasing implant insertion torque through preservation and densi cation of osteotomy site walls [14][15][16][17][18][19][20] . Since more bone particles will be present at the bone-implant interface when the implant bed is prepared with OD, it is expected to accelerate bone healing and, consequently, faster osseointegration 18,21 .…”
Section: Introductionmentioning
confidence: 99%